MODEL EKONOMI-EKOLOGI BERDASARKAN WTP PENGUNJUNG-WTA MASYARAKAT LOCAL DALAM PENGELOLAAN DESTINASI WISATA GUNUNG API BAWAH LAUT MAHENGETANG, KABUPATEN SANGIHE - Paulus Adrian Pangemanan; Gene H. M. Kapantouw (AGRI-SOSIOEKONOMI, 2017)
Continuing management of tourist destinations, integrating economic and ecological aspects, and involving quadrohelical roles: local communities, tourism businesses, government and universities. This research develops a tourism destination management model that integrates economic and ecological development based on visitor willingness to pay (WTP) attachment with willingness to accept (WTA) of local community, supported by business actor role and government. Colleges play a role in identifying ecological and economic elements, analyzing and formulating alternative development activities that ensure economic improvement for local communities and resource sustainability (natural, socio-cultural) to improve the destination's life cycle. The purpose of this research is to manage the role of quadrohelical tourism in evaluating, developing economic programs / activities for the surrounding community, by prioritizing the sustainability of resource ecosystem. This research was conducted for 10 months in the area of Mahengetang submarine volcano in Sangihe District. This study focuses on identifying existing conditions of economic and ecological elements, analysis and formulation of alternative activities for economic and ecological improvement based on indicators (WTP-WTA). Destination management model based on WTP-WTA with integrated role of quadrohelical system can be adapted and developed in other destination, or in other resource utilization.